2018
DOI: 10.1021/jacs.8b08826
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Mediated Amination of Aryl C–H Bonds with the Direct Use of Aqueous Ammonia via a Disproportionation Pathway

Abstract: The direct amination of C−H bonds with ammonia is a challenge in synthetic chemistry. Herein, we present a copper-mediated approach that enables a chelation-assisted aromatic C−H bond amination using aqueous ammonia. A key strategy was to use soft lowvalent Cu(I) species to avoid the strong coordination of ammonia. Mechanistic investigations suggest that the catalysis is initiated by a facile deprotonation of bound ammonia, and the C−N coupling is achieved by subsequent reductive elimination of the resultant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…The EPR of the precipitate obtained after mixing copper acetate with phthalimide in acetonitrile (Figure , 3) has the parameters of a broad line in the middle fields with g = 2.17, Δ H iso = 960 G, which is close to the values characteristic of copper acetate, although there are certain differences in the waveform, partial separation occurs. However, oxidation of the amine under the action of Cu­(II) or disproportionation to Cu­(I) and Cu­(III), which is sometimes stated in the aforementioned literature, is not observed …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EPR of the precipitate obtained after mixing copper acetate with phthalimide in acetonitrile (Figure , 3) has the parameters of a broad line in the middle fields with g = 2.17, Δ H iso = 960 G, which is close to the values characteristic of copper acetate, although there are certain differences in the waveform, partial separation occurs. However, oxidation of the amine under the action of Cu­(II) or disproportionation to Cu­(I) and Cu­(III), which is sometimes stated in the aforementioned literature, is not observed …”
Section: Results and Discussionmentioning
confidence: 99%
“…However, oxidation of the amine under the action of Cu(II) or disproportionation to Cu(I) and Cu(III), which is sometimes stated in the aforementioned literature, is not observed. 56 The EPR spectrum of the precipitate obtained after mixing Cu(OAc) 2 with phthalimide in acetonitrile and their combined oxidation is characterized by a signal characteristic of mononuclear Cu(II) complexes in the low-spin state of 3d. 9 The spectrum was simulated and the parameters of the spin Hamiltonian were obtained, which characterize the slightly distorted axial symmetry of the complex (Figure 7, 4, and Figure S7): g 1 = 2.27, a Cu = 170 G, ΔH 1 = 90 G; g 2 = 2.10, ΔH 2 = 120 G; g 3 = 2.04, ΔH 3 = 70 G; ⟨g⟩ ≈ 2.14.…”
Section: Which Canmentioning
confidence: 99%
“…Although ammonia strongly coordinates to metals, leading to catalyst poisoning, the introduction of an amino group into the ortho-position of oxazoline-derived aryl amides via C-H activation using aqueous ammonia was accomplished by aid of a soft, low-valent Cu(I) species (Scheme 75A and B) [339]. Preliminary studies suggested that the reaction mechanism involves disproportionation of the Cu(I) species leading to the in situ formation of a Cu(III) species, which results in an increased acidity of a copper-amido intermediate, thus allowing for the deprotonation of copper-bound ammonia and a reductive elimination step to give the product.…”
Section: Copper-catalyzed C-h Activationmentioning
confidence: 99%
“…Early examples of copper-promoted C−H activation of 2-arylpyridines were disclosed by Yu et al [12] and Chatami et al [13] independently. Inspired by these studies, various copper-induced C−H functionalizations, such as arylations, alkynylations, cyanations, aminations, nitrations, oxygenations, thiolations, halogenations, and phosphorylations, among others, were accomplished [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%